Thirty-day oral toxicity effect of high-dose dextromethorphan hydrodbromide (HBr) in BFAD : SD rat - Pagsanhan, Evangeline P.; Gutierrez, Oscar Jr.; Biares, Caroline Imelda B.; Calderon, Carlito J.
Dextromethorphan hydrobromide (HBr) is commonly abused in the form of syrup and in combination with other drugs. There has been no long-term toxicity study that would show the effects of the drug combinations when taken in a large single doses over a prolonged period of time. In this study, a comparison was made on the effects of a high doses of fixed-dose dextromethorphan (FDD) in combination with chlorpheniramine maleate, sodium citrate and phenylpropanolamine HCl (PAA) administered orally for 30 days in BFAD:SD rat with plain dextromethorphan (PD) in 60% sucrose. The test rats were allowed to recover for 7 days post-30 days treatment. Different parameters, such as animal observation, body weight, water and feed intakes, urinalysis, hematology, serum biochemistry, and gross pathology were used to compare baseline data and cumulative effects of FDD and PD. The results of the experiment showed manifestation of generalized pilomotor erection of all male and female rats administered with FDD which was not observed during the recovery period. One of the female subjects manifested bilateral nephromegaly with hydronephrosis. The generalized pilomotor erection is attributed to the symphathomimetic effect of PAA, an alpha-adrenergic agonist, on the smooth muscles of the roots of the hair. The bilateral nehpromegaly with hydronephrosis may be attributed to the sensitivity of the rat to PAA. Dextromethorphan HBr in combination with PAA administered over a prolonged period of time at high doses can induce nephromegaly with hydronephrosis in sensitive rats.(Author)
BFAD Laboratory Information Bulletin, 1996 2 (1) pages 1-5
Keywords: Dextromethorphan -- toxicity; Dextromethorphan Hydrobromide -- toxicity